2021
DOI: 10.1161/circresaha.120.318075
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hepatic Angiotensinogen Attenuates Sepsis-Induced Myocardial Dysfunction

Abstract: Rationale: The renin-angiotensin system (RAS) is a complex regulatory network that maintains normal physiological functions. The role of the RAS in sepsis-induced myocardial dysfunction (SIMD) is poorly defined. Angiotensinogen (AGT) is the unique precursor of the RAS and gives rise to all angiotensin peptides. The effects and mechanisms of AGT in development of SIMD have not been defined. Objective: To determine a role of AGT in SIMD and investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Elevated angiotensin II levels and imbalance with angiotensin-converting enzyme 2/Ang-(1-7)/Mas receptor in the liver induces hepatic ROS overproduction, lipid accumulation, and inflammation. A very recent study identified a liver-heart axis, showing that hepatocyte-derived, rather than locally synthesized, cardiac angiotensinogen, contributes to myocardial dysfunction in septic mouse models [11] . Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD [12] .…”
Section: The Mechanisms Underlying Nafld-related Cvd Must Be Further ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated angiotensin II levels and imbalance with angiotensin-converting enzyme 2/Ang-(1-7)/Mas receptor in the liver induces hepatic ROS overproduction, lipid accumulation, and inflammation. A very recent study identified a liver-heart axis, showing that hepatocyte-derived, rather than locally synthesized, cardiac angiotensinogen, contributes to myocardial dysfunction in septic mouse models [11] . Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD [12] .…”
Section: The Mechanisms Underlying Nafld-related Cvd Must Be Further ...mentioning
confidence: 99%
“…A very recent study identified a liver-heart axis, showing that hepatocyte-derived, rather than locally synthesized, cardiac angiotensinogen, contributes to myocardial dysfunction in septic mouse models. [11] Compelling evidence from animal and human studies suggests that heightened activation of the SNS is a key contributor to the development of NAFLD. [12] This lipolytic state, induced by sympathetic overactivity, results in increased levels of FFAs and triglycerides in the circulation and visceral deposition, which exacerbates NAFLD.…”
Section: Neuroendocrine Activationmentioning
confidence: 99%
“…Whether all the other pressure load conditions also lead to increased ACE2 expression is unknown. On the other hand, we assume that due to changes in sample sources, mouse samples did not reveal substantial differences [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of molecules predicted to be critical up stream regulators strongly support proinflammatory signaling activation in the POLG RV. For instance, lipopolysaccharide, AGT (angiotensinogen), INFG were all predicted to be activated and clearly stimulate inflammation (e.g., [25][26][27]. Similarly, Zc3h12c, the top predicted inhibited upstream regulator, has been implicated as an inhibitor of NF-kB (28).…”
Section: Discussionmentioning
confidence: 99%